A framework of green it capability maturity for it product lifecycle in UTM [electronic resource] - Tam Sakirin, 1985-; Azizah Abdul Rahman, upervisor (2014)
Thesis (Sarjana Sains (Teknologi Maklumat - Pengurusan)) - Universiti Teknologi Malaysia, 2014